Recurrent myocardial injury is a strong predictor of ICU mortality in COVID-19. (2nd May 2022) - De Roeck, F; Schepens, T; Schroyens, M; De Meyer, G; Jacobs, R; Dams, K; Robert, D; Jorens, PG
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Myocardial injury is common in COVID-19, and has been linked to disease severity and mortality.1 Its pathophysiology is not fully elucidated and suggested mechanisms include cytokine damage, endotheliitis, myocarditis, ferroptosis, acute coronary syndrome, oxygen supply-demand mismatch and pulmonary embolism.2-3 Elevated serum cardiac troponin (cTn) – as surrogate marker of myocardial injury – at admission and during hospitalisation is associated with poor outcome.4-5 Comparison of available trial data, however, is unfeasible, because of variable definition and sampling timing/intervals/assays.6 Peculiarly, prognostic cut-off cTn values are often – retrospectively – set much lower than recommended by the guidelines.6-8 Furthermore, robust intensive care unit (ICU) outcome data regarding cTn evolution over time is lacking. Purpose: The aim of this study is to critically explore the correlation between myocardial injury and mortality in a tertiary ICU population, using both standard and high cTn cut-off values, and to scrutinise the impact of timing and recurrence. Methods: All adult COVID-19 patients admitted to our tertiary ICU between 06/03/2020 and 27/09/2021 were enrolled in this large, retrospective, single centre, cohort study. Patients requiring extracorporeal membrane oxygenation (n=29) were excluded. Myocardial injury was defined – as per ESC guidelines - as high-sensitive cardiac troponin I (hs-cTnI) peak >45ng/L (99th percentile upper reference limit) and 'major' myocardial injury was defined as hs-cTnI >135ng/L (3x upper limit of normal).6-7 Recurrent myocardial injury was considered if a new hs-cTnI peak above cut-off point occurred after normalisation. Patients were categorised according to peak ('standard' >45ng/L vs 'high' >135ng/L), onset ('on admission' vs 'during hospitalisation') and recurrence ('single' vs 'multiple') of hs-cTnI rise. Statistical analysis was done by logistic regression, using IBM SPSS version 28. Results: A total of 193 COVID-19 ICU patients were included. Patient characteristics, disease severity indices and treatment details are summarised in Table 1. The mean age was 62 years and ICU mortality was 22%. Myocardial injury overall occurred in 51% (n=99) and major myocardial injury occurred in 39% (n=75) of patients. Obtained results were consistent across standard (>45ng/L) and high (>135ng/L) hs-cTnI cut-off groups. Myocardial injury only present at ICU admission was not correlated with mortality in our cohort, contradicting prior (mostly non-ICU) trials. Single hs-cTnI peak during ICU hospitalisation, however, and, especially recurrent hs-cTnI peaks were strong predictors of ICU mortality. The respective incidence, odds ratio, 95% confidence intervals and p-values are displayed in Table 2. Conclusion: Myocardial injury occurring during ICU hospitalisation and, especially, recurrent myocardial injury is strongly correlated with ICU mortality in COVID-19 patients.